De La Haine à la compassion (Barrio), deux visions des quartiers au cinéma - Pascale Thibaudeau (Cahiers de Civilisation Espagnole Contemporaine)
This compared analysis of both movies La Haine (Mathieu Kassovitz, 1995) and Barrio (Fernando León de Aranoa, 1998) highlights, thanks to precise examinations, the very distinct influence the French movie had on the Spanish movie, also allowing to focus on the characteristics of each being linked to a specific national context. This anchor determines two very different cinematic representations of the outlying districts, carried by two almost opposed views.